Study of energetic balance of the hydraulic system with fixed displacement pump and pressure relief valve - О. Levchenko (Mechanics and Advanced Technologies, 2017)
It was analyzed the basic schematics implementing energy level of industrial hydraulic systems. It was considered the structure and composition of the hardware system of fixed displacement pump and pressure relief valve with manual control. It was carried out a study of the energy balance of the hydraulic system of fixed displacement pump and pressure relief valve at 5 possible positions opening cross-section of adjustable throttle valve. For each of the provisions specified size and power consumption efficiency, as well as the value of energy loss of the hydraulic system. It is established distribution of energy losses between the actuator, pump, throttle valve and pressure relief valve under different operating conditions selected hydraulic system. The change in energy efficiency and the efficiency of the hydraulic system was determined under different operating conditions. Graphs change energy balance was built throughout the range of adjustment of the hydraulic system of fixed displacement pump and pressure relief valve.